Localisation of a gene for an autosomal recessive syndrome of macrocephaly, multiple epiphyseal dysplasia, and distinctive facies to chromosome 15q26 - Bayoumi, R. (BMJ Group, 2001)
BACKGROUND—We have previously described an autosomal recessive syndrome of macrocephaly, multiple epiphyseal dysplasia (MED), and distinctive facies in a large, extended Omani family. The MED observed seems to be part of a larger malformation syndrome, since both craniofacial and central nervous system changes were present in the family. We performed a whole genome scan in this family in order to identify the gene locus for this malformation syndrome. METHODS AND RESULTS—Using homozygosity mapping, we show linkage to the telomeric region of the long arm of chromosome 15. The position of both the disease gene and the principal glycoprotein, chondroitin sulphate proteoglycan (aggrecan, AGC1) on chromosome 15q26, suggested that the aggrecan gene is a candidate for the disease in this family. However, three of the four affected children were heterozygous for a polymorphism at position 831 of the coding sequence of AGC1, providing strong evidence against its involvement. CONCLUSION—We have identified a gene locus for a recessive syndrome of macrocephaly, MED, and distinctive facies in a large Omani family. Aggrecan located on chromosome 15q26, within the critical region determined for this syndrome in this family, was excluded as a candidate gene.   Keywords: macrocephaly; multiple epiphyseal dysplasia; distinctive facies; chromosome 15q26